Interdisciplinary interprofessional education using an online learning environment called values exchange: A qualitative investigation. Issue 3 (27th April 2022) - McInerney, John; Seedhouse, David; Pettit, Michael; Roberts, Simone; Druva, Ruth; Lewicki, Sabrina
Abstract: Introduction: Interprofessional education (IPE) is implemented throughout the curricula of student healthcare professions as it is understood to provide positive impact on patient outcomes in the clinical environment. There are different methods to provide IPE such as through online learning or traditional face‐to‐face methods. However, there is a lack of research surrounding the use of Online Learning Environments (OLEs) to teach IPE. Methods: In a pilot study, seventy‐one undergraduate radiography students and twenty Master of Pharmacy students engaged in an ethical scenario using the OLE, Values Exchange (Vx). Following the activity, students were invited to complete an open‐ended response question. Fourteen students responded and these data were used for qualitative analysis. Results: A thematic analysis of the students' open‐ended responses found the emergence of three major themes, namely; understanding the roles of other healthcare professionals, developing self‐reflection skills and, preparing for the clinical environment. Students suggested that additional time allocated for undertaking the study would benefit their engagement in the activity. Students would benefit from added engagement in the Vx task in both the short and long term for IPE. Conclusion: Students are receptive in utilising contemporary approaches such as OLEs in furthering their IPE. Positive interpretations and suggestions by both radiography and pharmacy students in this study demonstrate how Vx as an OLE teaching tool can be used effectively. OLEs can overcome barriers that exist in face‐to‐face education experiences. OLEs should be considered for greater use within academic curricula of healthcare professions, but only if they have been evaluated for effectiveness. Abstract : This is an original qualitative research article. It was conducted across two professions, across two geographical locations. The project examined the perspectives of Master of Pharmacy students in England and undergraduate Radiography students in Australia in relation to the effectiveness of an online learning environment to facilitate interprofessional learning.